Potential impact of national recommendations to use short course antibiotic therapy on antibiotic use in the emergency department of a UK hospital: retrospective observational study. Issue 2 (12th November 2021) - Powell, Neil; Wade, Liam; Iqbal-elahi, Rumaysah; McDonald, Caitlin; Philips, Ryan; Owens, Rhys; Amir, Amani; Cho, Steven; Nampa, Tracy; Lim, Deborah; Tai, Kevin; Jadav, Mark
Abstract : Background and importance: The National Institute for Health and Care Excellence (NICE) antimicrobial prescribing guidelines for common infections recommend short course antimicrobial therapy in order to reduce antibiotic associated harm. Objective: To quantify the opportunity to reduce antibiotic use in an emergency department (ED) through adoption of these short antibiotic course recommendations. Design, settings and participants: A retrospective observational study in an ED in the UK with 95 000 attendances a year. Patients managed in the ED between 1 December and 31 December 2019 with the following infections were identified: acute otitis media, human and animal bites, pyelonephritis, lower urinary tract infections, cellulitis, cough, infective exacerbation of chronic obstructive pulmonary disease, pneumonia, sore throat, sinusitis, and diverticulitis. Outcome measure: Excess antibiotic use due to either a protracted course length, or not meeting criteria for antibiotics. Results: 395 patients (260 adults and 135 children) were identified. Of the 1215 days of antibiotic therapy, 198 (16%) were excess because of protracted course lengths. In terms of antibiotic defined daily doses (DDD), there were 1201.5 antibiotic DDD prescribed, of which 232 (19%) DDD were excess because of protracted course lengths. If both protracted courses and unnecessary antibiotic use were included, then 321 (27%) DDD were excess. Excess antibiotic use and total antibiotic use by infection group were: 123/546 (23%) DDD in lower respiratory tract infection, 46/59 (79%) in upper respiratory tract infection, 44/231 (19%) in upper and lower urinary tract infection, 0/113 (0%) cellulitis, 77/180 (43%) bites, and 30/40 (75%) diverticulitis. Excess antibiotic use, as a proportion of all antibiotic use in the ED, was 321/4291 (7.5%) DDD, and of whole hospital antibiotic use, the ED's excess use was 321/33 566 (0.96%). Conclusion: Adoption of NICE antibiotic prescribing guidelines for common infections has the potential to reduce total antibiotic use in the ED by 7.5% and contribute to the hospital-wide antibiotic stewardship programme.